What rules? Framing the governance of artificial agency. Issue 2 (7th July 2021) - Gahnberg, Carl
ABSTRACT: Artificial Intelligence (AI) is not new, but recent years have seen a growing concern about the technology's political, economic and social impact, including debates about its governance. This paper describes how an analysis of the technology's governance should build on the understanding of AI as the creation of artificial agents, and that the challenge that governance seeks to address is best understood as one of material agency. It describes how relevant rules can be systematically analyzed across different applications by considering the fundamental properties of artificial agents. The paper concludes by describing how the framework can be applied for further governance studies, and as a means to bridge insights across social science and technical perspectives on AI.